(untitled) - Taylor, Gordon Rattray (London, 1968)
The book explores the world of the future, and speculates about things such as cloning, biological warfare and man's quest for immortality. Bizarre, hilariously dated, and at times, oddly prophetic. A very entertaining read.
Keywords: Biological time-bomb,Bom sinh hojc